Enhancing Brand Identity and Purchase Intention through Digital Marketing Strategy - Lady Lady; Cristina Anggrena; Hepy Hefri Ariyanto; Ronny Firdiansyah Arief (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2026)
Addressing the limited empirical evidence on the